Configuring ecosystem strategies for digitally enabled process innovation: A framework for equipment suppliers in the process industries. (July 2021) - Kamalaldin, Anmar; Sjödin, David; Hullova, Dusana; Parida, Vinit
Abstract: Digitalization offers new opportunities for equipment suppliers to support the competitiveness of process industry firms through participating in digitally enabled process-innovation initiatives. However, doing so is not without challenges as it requires equipment suppliers to align with multiple actors within an extended ecosystem to deliver complex product-service software systems as embodied sources of process innovation. This creates various challenges for the equipment supplier because it has to secure its role in an ecosystem where it must simultaneously cooperate and compete with other ecosystem actors. Therefore, it needs to consciously determine what ecosystem strategy to apply. Using multiple exploratory case studies, we investigate how equipment suppliers configure appropriate ecosystem strategies to realize digitally enabled process innovation for process industry firms. Our findings emphasize that different industrial customer contexts require different ecosystem strategies; we have identified four archetypical ecosystem strategies (orchestrator, dominator, complementor, and protector). The core insights from our research are converted into a decision tree framework to guide equipment suppliers in configuring the appropriate ecosystem strategy based on the industrial customer context. Key contingency considerations include determining an appropriate role in the ecosystem (leader or follower) and a suitable coopetitive approach (cooperation dominated or competition dominated). Highlights: Different industrial customer contexts require different ecosystem strategies. 4 archetypical ecosystem strategies: orchestrator, dominator, complementor, protector. Key consideration is determining the role in the ecosystem (leader or follower). Another key factor is the coopetitive approach (cooperation or competition dominated). We present a decision tree to help suppliers configure appropriate ecosystem strategy.